Introdução da noção de variável em expressões algébricas por meio da resolução de problemas: Uma abordagem dinâmica - Christo, Danilo dos Santos (2006)
Students difficulties in writing and interpreting algebraic language, particularly in comprehending the meaning of variable have been discussed by such researchers as Kieran, Küchemann, Arcavi and others. In this research, we evaluate a teaching proposal in which it is aimed at explaining established relations between elements of circumstances of proportionality and generalizable arithmetic expressions. This analysis of regularity eases the algebraic language teaching through a dynamic approach in which the notion of dependence among the circumstantial variables is emphasized. This proposal was applied to a sixth grade group of a public primary school in São Paulo city. The analysis of the obtained results allows us to verify the teaching proposal s efficiency for attaining the objectives of this research and provides tools for training teachers